Metastatic Bone Pain Palliation using 177 Lu-Ethylenediaminetetramethylene Phosphonic Acid - Mehrosadat Alavi; Shapour Omidvari; Alireza Mehdizadeh; Amir Jalilian; Ali Bahrami-Samani (World Journal of Nuclear Medicine)
177 Lu-ethylenediaminetetramethylene phosphonic acid (EDTMP) is presently suggested as an excellent bone seeking radionuclide for developing metastatic bone pain (MBP) palliation agent owing to its suitable nuclear decay characteristics. To find the exact dosage and its efficiency, this clinical study was performed on the human being, using 177 Lu-EDTMP for MBP palliation. 177 Lu-EDTMP was prepared by Iran, atomic energy organization. Thirty consecutive patients with determined tumors, incontrollable MBP, and positive bone scan at 4 weeks before the beginning of the study participated in this study in the nuclear medicine ward. 177 Lu-EDTMP in the form of sterile slow IV injection was administered with a dose of 29.6 MBq/kg. Short form of brief pain inventory questionnaire was used to evaluate the efficiency of the intervention. Questionnaires were filled out by an expert nuclear physician every 2 weeks while the cell blood count was also checked every 2 weeks up to 12 weeks for evaluation of bone marrow suppression and hematological toxicity. Furthermore, whole body scan was done at days 1, 3, and 7. Twenty-five patients showed a significant pain relief since 2 weeks after the injection, and continued until the end of the follow up period (12 weeks). There were no significant early complications such as bone marrow suppression, hematological toxicity, and no systemic adverse effects. No complication was observed in renal function. Twenty one patients showed flare phenomenon that was started after the 12.2 ± 1.78 h lasting for 38.4 ± 23.08. Sixteen patients (53%) were completely treated; nine patients (30%) showed a partial response, and five patients (17%) had no response to treatment. Total response to treatment was achieved in 25 patients (83%). At the end of the evaluation, no bone marrow suppression or hematologic toxicity was observed. 177 Lu-EDTMP has shown suitable physical and biological properties with good results in long term bone pain relief for patients with bone metastasis.